Młodopolski antymoralista w powieści Bez dogmatu Henryka Sienkiewicza - Kranc, Ilona (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Young Poland’s antimoralist in Henry Sienkiewicz’s novel titled Bez dogmatu was dedicated to Leon Płoszowski, the main character of said work. It consists of three parts. The starting point is assessing the themes of literary works written by Sienkiewicz and setting Bez dogmatu midst his other creations, which are settled in Polish sensibleness. Nevertheless, it is not this study’s intention to recall and present biographical information. Next part has been devoted to characterising the demeanour of Płoszkowski in respect of his amorality. The point of ‘without-dogmatism’ was also raised, which other main characters of many Sienkiewicz’s works can also be distinguished by. Though this topic was quite limited in order not to obscure the main matter. Last segment was devoted to the literary criticism that precisely evaluated Sienkiewicz’s ‘without-dogmatism’, the depicted attitudes of the foremost critics of Płoszowski’s, as well as reckoning up the author with his own work.
Young Poland’s antimoralist in Henry Sienkiewicz’s novel entitled Bez dogmatu
Keywords: novel; literary hero; stereotype; controversy; worldview